The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/gox.0000000000002153
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Translation, Cultural Adaptation, and Validation of the Standardized Cosmesis and Health Nasal Outcomes Survey Questionnaire

Abstract: Background: The Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) questionnaire is a new instrument that was developed to evaluate both functional and cosmetic components of rhinoplasty. It is a reliable, consistent, and validated patient-reported outcome measure that is not available in Spanish. Methods: The SCHNOS questionnaire was forward translated, back translated, and culturally adapted following international guidelines. Its psychometric validity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…The mean (standard deviation [SD]) preoperative NOSE, SCHNOS-O, and SCHNOS-C score of 69 (19) [9], P < .05).…”
Section: Functional Subgroupmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean (standard deviation [SD]) preoperative NOSE, SCHNOS-O, and SCHNOS-C score of 69 (19) [9], P < .05).…”
Section: Functional Subgroupmentioning
confidence: 99%
“…Among the quality-of-life (QOL) instruments' currently available for both aesthetic and functional rhinoplasty, the SCHNOS, which has been developed with a robust development technique, 3 is more precise, 2 more comprehensive, 4 and has been the most extensively validated. [5][6][7][8][9][10] The SCHNOS-O can be utilized as both a clinical and a screening tool for nasal obstruction, and the SCHNOS-C is a reliable clinical tool for cosmetic outcomes. 5 The twofactor structure of SCHNOS has been verified by confirmatory factor analysis, 6 and also demonstrated that two of the 10 SCHNOS items, item 1 (having a blocked or obstructed nose) and item 9 (how well the nose suits the face can be employed as a quick screening tool for the evaluation of nasal obstruction and assessing cosmetic disadvantage, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 SCHNOS has been already validated in several languages such as Arabic, French, Turkish, Spanish, and Brazilian Portuguese, lacking a European Portuguese version, as previously discussed. 10,[13][14][15][16] The small number of participants can be a limitation of this study, although several similar translation studies achieved a validation process with a similar number of participants. [13][14][15] Since our results showed the reliability and validity of the European Portuguese SCHNOS, we consider that a more robust association could only be stronger with a greater sample size.…”
Section: Discussionmentioning
confidence: 99%
“…21 The SCHNOS was translated and validated in several languages. [22][23][24] In conclusion, the use of easy-to-use screening tools for BDD can contribute toward improved patient care. Therefore, they should be routinely implemented in the preoperative assessment of rhinoplasty patients.…”
Section: Picavetmentioning
confidence: 99%